Descripción de una fauna marina paleocena procedente de Tierra del Fuego (Argentina) (Ameghiniana, 2013)
Six new species of Pelecypods and one undetermined Schizaster from the right bank of the upper river Ewan, Tierra del Fuego, are described. Their age is considered Paleocene.